Assessment of microbial loads of the Plankenburg and Berg Rivers and the survival of escherichia coli on raw vegetables under laboratory conditions - Barr, Alison; Ackermann, Alison (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc Food Sc (Food Science))--University of Stellenbosch, 2010.